Determination of Photochemical Screening, Antimicrobial and Antioxidant Activity of Citrus Maxima Peel - Hasan Khan, Naeem; Jia Qian, Chin; Perveen, Nabila (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
Citrus maxima (pomelo) proved to exhibit anti-microbial activity toward several microorganism strains although the negative result shown in this research conducted. There are several factors which can affect their antimicrobial activity such as resistance of tested bacterial strains, variation of temperature of preparation condition and low concentration of phytochemical present in the plant extract. Malaysia is popular for growth of “Citrus maxima” with the local name of pomelo. Pomelo is helpful in boosting body immune system, prevent weight gain and as anti-aging agent. Pomelo is also useful in preventing constipation as to promote digestion and peristalsis. Pomelo contains a huge amount of potassium (an effective vasodilator) and vitamin C (an antioxidant). Maceration and Soxhlet extraction of peel of Citrus maxima were carried out with n-hexane. Anti-microbial activity of Citrus maxima was followed by “Well Diffusion” method and comparing the clear inhibition zone of standard antibiotic and the extracts on “Mullen-Hinton agar”. Anti-oxidant activity of Citrus maxima was carried out by using DPPH radical-scavenging activity of total phenol assay. The qualitative test for alkaloids confirmed in all the extracts. The presence of terpenoids observed in filtrate and residue after maceration while terpenoids were absent in the Soxhlet sample. Presences of Flavonoids were found only in residue. Total phenolic compounds present in the hexane extract and found that higher the sample concentration, the higher the GAE value obtained.